Technical and financial valuation of hydrokinetic power in the discharge channels of large hydropower plants in Colombia: A case study (2016)
This work presents an assessment of the potential use of hydrokinetic turbines in the discharge channels of large hydroelectric power plants in Colombia. The assessment is performed at a pre-feasibility stage in order to evaluate the technical and financial potential of using hydrokinetic devices as a way to exploit kinetic energy in such channels. As a case study, two large hydropower plants were selected, one operated by a Francis turbine and the other operated by a Pelton turbine. The analysis assessed the hydraulic characteristics of the channels and the corresponding discharge flows. A prefeasibility financial analysis in an environment of uncertainty was also carried out using Monte Carlo simulation. The results show that the technology is not currently feasible for the Colombian market conditions, but the situation should be monitored in order to identify the right time for its optimal use in the future. The proposed methodology can be applied to research the feasibility of hydrokinetic energy for other kinds of applications.